2017
DOI: 10.1038/s41598-017-18113-3
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor alpha agonist suppresses neovascularization by reducing both vascular endothelial growth factor and angiopoietin-2 in corneal alkali burn

Abstract: We investigated the effect of a peroxisome proliferator-activated receptor alpha (PPARα) agonist ophthalmic solution in wound healing using a rat corneal alkali burn model. After instillation of a selective agonist of PPARα, fenofibrate, onto the burned cornea, PPARα-positive cells were observed in vascular endothelial cells, and there was upregulation of mRNA of PPARα in corneal stroma. Fenofibrate suppressed expression of neutrophils and macrophages during the early phase, and development of neovascularizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 41 publications
(36 reference statements)
5
40
0
Order By: Relevance
“…This implies PPARα activation could have potential for use as a preventive agent in patients with high risk of dry eye. Other cornea studies indicated therapeutic roles of PPARα agonists against corneal inflammation and neovascularization [ 110 , 111 ]. Corneal neovascularization is closely related to a reduction in corneal transparency which is important for visual acuity [ 112 , 113 ].…”
Section: Functions Of Pparα In the Eyementioning
confidence: 99%
See 1 more Smart Citation
“…This implies PPARα activation could have potential for use as a preventive agent in patients with high risk of dry eye. Other cornea studies indicated therapeutic roles of PPARα agonists against corneal inflammation and neovascularization [ 110 , 111 ]. Corneal neovascularization is closely related to a reduction in corneal transparency which is important for visual acuity [ 112 , 113 ].…”
Section: Functions Of Pparα In the Eyementioning
confidence: 99%
“…Corneal neovascularization is closely related to a reduction in corneal transparency which is important for visual acuity [ 112 , 113 ]. In rat corneal alkali burn models, corneal neovascularization was seen and a topical injection of fenofibrate suppressed its neovascularization through upregulation of PPARα mRNA expression and suppression of IL-6, IL-1β, Vegf and Ang-2 mRNA expressions [ 110 , 111 ].…”
Section: Functions Of Pparα In the Eyementioning
confidence: 99%
“…48,49 For example, fenofibrate can be compounded as an ophthalmic solution for treating corneal alkali burn in rats. 50 Accordingly eye drops containing either fenofibrate (50, 100, 200, 500 lM) or just its vehicle were administered daily to determine if they could reverse declines in lipid metabolism in 10-day corneas. Only 200 and 500 lM fenofibrate significantly increased PPARa gene expression (data not shown).…”
Section: Fenofibrate Reverses Declines In Lipid Metabolism In Sde Moumentioning
confidence: 99%
“…After the 2-weeks of acclimation, 8-week old rats were subjected to corneal alkali burn as described previously [50]. In brief, rats were anesthetized with 3.5% isoflurane in a 2:1 N 2 O/O 2 mixture.…”
Section: Corneal Alkali Injury (Cai) Modelmentioning
confidence: 99%